The Embodied Self - Pollack, Robert (Columbia Journal of Gender and Law, 2014)
So now I wish to address a question raised by my experience then, in the reflective context of this celebration of Pat’s professorship, my fifty-first anniversary of life with my wife, the artist, Amy Pollack, and my two decades since that seminar as a teacher and scientist versed in molecular biology, neurobiology, and evolution, as well as the notions of my own religion. The question is this: have we a “self” that is in any way separable from the body?